2018
DOI: 10.1097/pep.0000000000000532
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapists' Use and Alteration of Standardized Assessments of Motor Function in Children

Abstract: Purpose: This study presents survey responses of pediatric physical therapists' use and alteration of standardized assessments of motor function in children aged 2 to 10 years. Methods: Electronic and paper surveys were distributed to practicing physical therapists through the APTA Academy of Pediatric Physical Therapy electronic newsletter and 2 national conferences. Data were analyzed by response frequencies, qualitative responses, and χ2analyses for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…Nevertheless, the participants of this study also considered OMT applicability based on a patient's conditions as the third enabler of OMT usage. Furthermore, the other enablers agreed to by this study's participants, (i.e., validity and reliability of OMTs, and quick completion of OMTs), coincide with the study's findings conducted by Fay et al (2018) . They reported that most respondents consider the ease of completion and the assessment tools' quality/statistical/psychometric properties.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Nevertheless, the participants of this study also considered OMT applicability based on a patient's conditions as the third enabler of OMT usage. Furthermore, the other enablers agreed to by this study's participants, (i.e., validity and reliability of OMTs, and quick completion of OMTs), coincide with the study's findings conducted by Fay et al (2018) . They reported that most respondents consider the ease of completion and the assessment tools' quality/statistical/psychometric properties.…”
Section: Discussionsupporting
confidence: 83%
“…Two studies support this finding as they reported GMFM as the most frequently used OMT from their surveys ( Hanna et al, 2007 ; Knox et al, 2019 ). Similarly, Fay et al (2018) cited GMFM as the second most used OMT in their study. Moreover, Thomason and Wilmarth (2015) mentioned GMFM as the most reported additional OMT used in school-based PT services in preschool, elementary, and middle-/high-school students.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…5 Pediatric PTs utilize OMTs to quantify children's motor skills and functional development that serves as a basis for establishing a course of treatment necessary for maximal function. 6 In determining the most appropriate outcome measure, Coster 7 reported that it is necessary to consider factors such as dimension, format, reliability, responsiveness, and feasibility of the outcome measure. Common OMTs, according to the American Physical Therapy Association's (APTA), include children's assessment of participation and enjoyment (CAPE) and preferences for activities in children (PAC), CP functional classification systems, and gross motor function measure (GMFM).…”
Section: Introductionmentioning
confidence: 99%